2017
DOI: 10.2147/ott.s126051
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the androgen receptor in triple-negative breast cancer: current perspectives

Abstract: Triple-negative breast cancer (TNBC) is an aggressive subtype associated with frequent recurrence and metastasis. Unlike hormone receptor-positive subtypes, treatment of TNBC is currently limited by the lack of clinically available targeted therapies. Androgen signaling is necessary for normal breast development, and its dysregulation has been implicated in breast tumorigenesis. In recent years, gene expression studies have identified a subset of TNBC that is enriched for androgen receptor (AR) signaling. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 108 publications
(160 reference statements)
3
40
1
1
Order By: Relevance
“…reported that a high density of intratumoral FOXP3+ cells was associated with longer overall survival but not with stromal infiltration . In our study, lower TILs scores were observed in the AR+ subclass of TNBC, which is considered to be a prime candidate for anti‐androgen and CDK4/6 inhibition therapies . However, no differential expression of TILs or various immune cell subtypes was observed with regard to subclassification of TNBC into basal‐like and non‐basal‐like groups …”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…reported that a high density of intratumoral FOXP3+ cells was associated with longer overall survival but not with stromal infiltration . In our study, lower TILs scores were observed in the AR+ subclass of TNBC, which is considered to be a prime candidate for anti‐androgen and CDK4/6 inhibition therapies . However, no differential expression of TILs or various immune cell subtypes was observed with regard to subclassification of TNBC into basal‐like and non‐basal‐like groups …”
Section: Discussioncontrasting
confidence: 43%
“…36 In our study, lower TILs scores were observed in the AR+ subclass of TNBC, which is considered to be a prime candidate for anti-androgen and CDK4/6 inhibition therapies. 37,38 However, no differential expression of TILs or various immune cell subtypes was observed with regard to subclassification of TNBC into basal-like and non-basal-like groups. 17 High expression of CD68 was significantly associated with worse outcome in patients with luminal B tumours, which may explain, at least in part, the distinct roles of TILs subpopulations in different BC subtypes.…”
Section: Discussionmentioning
confidence: 96%
“…In the current study, TNBC AR+ has lower proliferation rates and lower histological grade compared with QNBC. This approximated to the range of previously published studies (Traina et al, 2018;Sutton et al, 2012;Thike et al, 2014;Anand et al, 2017;Mina et al, 2017).…”
Section: Discussionsupporting
confidence: 60%
“…About 50%-80% of invasive breast cancers (regardless of ER status) express AR and recent studies indicate AR expression is positively associated with a good prognosis. In addition, recent studies showed that AR-expressing triple-negative breast cancer (TNBC) is dependent on AR signaling; thus, targeting AR seems to improve outcomes in TNBC (1)(2)(3)(4)(5)(6)(7). Despite the prevalence and clinical significance of AR expression in breast cancer, preclinical evidence supporting the use of ARtargeting agents and potential biomarkers of response to AR inhibitors in breast cancer are lacking (4).…”
Section: Introductionmentioning
confidence: 99%